3 Bernard Bush, Laws of the Royal Colony of New Jersey 5 (1980); see also 1753 N.J. Laws ch. 257; 1766 N.J. Laws ch. 422; 1770 N.J. Laws ch. 520; 1771 N.J. Laws ch. 539 - (:unkn) unknown (My University, 1746)
Each militiaman between the Age of Sixteen and Fifty Years" must "be sufficiently armed with one good sufficient Musket or Fuzee well fixed, a Sword or Bayonet, a Cartouch-Box or Powder-Horn," plus bullets and powder.
Keywords: MILITIAS